NaHBEt3-Catalyzed 1,2-Hydroboration of α,β-Unsaturated Carbonyls: Mechanistic Insights into Hydride Transfer Pathways - Mangina, N. S. V. M. Rao; Park, Sehoon (Synthesis, 2025)
A highly 1,2-selective hydroboration of α,β-unsaturated ketones and aldehydes has been achieved by employing simple and readily available, transition metal-free NaHBEt3 as a catalyst. This sodium-catalyzed reaction proceeds at room temperature, exclusively furnishing the corresponding allylic alcohols with broad substrate scope and excellent functional group tolerance, including nitrile, amine, esters, nitro groups, alkoxy groups, and halides. Mechanistic studies suggest that (i) BEt3 serves as a Lewis acid cocatalyst, activating the substrate and facilitating the reaction, (ii) the resting hydride species are H2Bpin and (EtO)HBpin, and (iii) the rate-determining step involves hydride transfer from these resting species to the carbonyl carbon.
Keywords: Alkali metal catalyst; 1,2-Reduction; α,β-Unsaturated carbonyls; Allylic alcohols; Hydride transfer pathway